Illuminated Manuscript Production in Medieval Iceland - Drechsler, Stefan (Brepols, 2025)
This book examines a cultural revolution that took place in the Scandinavian artistic landscape during the medieval period. Within just one generation (c. 1340–1400), the Augustinian monastery of Helgafell became the most important centre of illuminated manuscript production in western Iceland. By conducting interdisciplinary research that combines methodologies and sources from the fields of Art History, Old Norse-Icelandic manuscript studies, codicology, and Scandinavian history, this book explores both the illuminated manuscripts produced at Helgafell and the cultural and historical setting of the manuscript production. Equally, the book explores the broader European contexts of manuscript production at Helgafell, comparing the similar domestic artistic monuments and relevant historical evidence of Norwich and surrounding East Anglia in England, northern France, and the region between Bergen and Trondheim in western Norway. The book proposes that most of these workshops are related to ecclesiastical networks, as well as secular trade in the North Sea, which became an important economic factor to western Icelandic society in the fourteenth century. The book thereby contributes to a new and multidisciplinary area of research that studies not only one but several European cultures in relation to similar domestic artistic monuments and relevant historical evidence. It offers a detailed account of this cultural site in relation to its scribal and artistic connections with other ecclesiastical and secular scriptoria in the broader North Atlantic region.